Characterizations of the diurnal shapes of OI 630.0 nm dayglow intensity variations: inferences - Chakrabarty, D.; Sekar, R.; Chandra, H.; Narayanan, R.; Pathan, B.M.; Subbarao, K.S.V. (My University, 2002)
Measurements of OI 630.0 nm thermospheric dayglow emission by means of the Dayglow Photometer (DGP) at Mt. Abu (24.6° N, 73.7° E, dip lat 19.09° N), a station under the crest of Equatorial Ionization Anomaly (EIA), reveal day-to-day changes in the shapes of the diurnal profiles of dayglow intensity variations. These shapes have been characterized using the magnetometer data from equatorial and low-latitude stations. Substantial changes have been noticed in the shapes of the dayglow intensity variations between 10:00–15:00 IST (Indian Standard Time) during the days when normal and counter electrojet events are present over the equator. It is found that the width (the time span corresponding to 0.8 times the maximum dayglow intensity) of the diurnal profile has a linear relationship with the integrated electrojet strength. Occasional deviation from this linear relationship is attributed to the presence of substantial mean meridional wind.
Keywords: Ionosphere; Ionospheric disturbances; Equatorial electrojet; Atmosphere interactions; EEJ electric field